A Critical Review of Open Innovation in SMEs: Implementation, Success Factors and Challenges - Eristian Wibisono (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
AbstractThis literature review explores the Open Innovation of SME companies, their application, success factors, impact, and challenges. The theoretical framework is built starting from the definition, a critical pillar, and Open Innovation in SME companies. The main factor in the Open Innovation process stage is finding innovative ideas and establishing network access with the external environment. Balanced, systematic, and thorough collaboration is the key to this process. Although European scholars have done it quite a lot, the study of literature on Open Innovation in SMEs still could continue to be developed. Several research results were found in studies conducted in developing countries such as China, Taiwan, and Korea, distinguishing them from similar studies in Europe.Keywords: innovation; SMEs; technology; entrepreneurship; open innovation